Excessive Accumulation of Intracellular Ca2+ After Acute Exercise Potentiated Impairment of T-cell Function - Liu, Renyi; Krüger, Karsten; Pilat, Christian; Fan, Wei; Xiao, Yu; Seimetz, Michael; Ringseis, Robert; Baumgart-Vogt, Eveline; Eder, Klaus; Weissmann, Norbert; Mooren, Frank Christoph (Frontiers in Physiology, 2021)
Ca2+ is an important intracellular second messenger known to regulate several cellular functions. This research aimed to investigate the mechanisms of exercise-induced immunosuppression by measuring intracellular calcium levels, Ca2+-regulating gene expression and agonist-evoked proliferation of murine splenic T lymphocytes. Mice were randomly assigned to the control, sedentary group (C) and three experimental groups, which performed a single bout of intensive and exhaustive treadmill exercise. Murine splenic lymphocytes were separated by density-gradient centrifugation immediately (E0), 3h (E3), and 24h after exercise (E24). Fura-2/AM was used to monitor cytoplasmic free Ca2+ concentration in living cells. The combined method of CFSE labeling and flow cytometry was used for the detection of T cell proliferation. The transcriptional level of Ca2+-regulating genes were quantified by using qPCR. Both basal intracellular Ca2+ levels and agonist-induced (ConA, OKT3, Thapsigargin) Ca2+ transients were significantly elevated at E3 group (p < 0.05 vs. control). However, mitogen-induced cell proliferation was significantly decreased at E3 group (p < 0.05 vs. control). In parallel, the transcriptional level of PMCA, SERCA, TRPC1 and P2X7 was significantly downregulated, the transcriptional level of IP3R2 and RyR2 was significantly upregulated in E3 (p < 0.01 vs. control). In summary, this study demonstrated that acute exercise affected intracellular calcium homeostasis, most likely by enhancing transmembrane Ca2+ influx into cells and by reducing expression of Ca2+-ATPases such as PMCA and SERCA. However, altered Ca2+ signals were not transduced into an enhanced T cell proliferation suggesting other pathways to be responsible for the transient exercise associated immunosuppression.